PERBEDAAN SHEAR BOND STRENGTH DUA MACAM KOMPOSIT RESIN PADA DENTIN DENGAN DUA BAHAN BONDING YANG BERBEDA - Stephani Dwijanti; Ansar Basar; Gatot Sutrisno; Ali Noerdin (Journal of Dentistry Indonesia, 2015)
The aim of this in vitro study was to evaluate the shear bond strength of resin composite materials to dentin by using different bonding agents. Forty human premolars were selected for the study, and cylindrical posts of either Spectrum TPH and Charisma were bonded vertically to a standard flat dentinal area, prepared on the buccal surface. A chisel-shaped shearing blade, attached to the crosshead of a universal mechanical testing machine. The shear bond strength to dentin of 10 resin composite-dentin adhesive combinations were measured. The results showed that the bond strength values of dentin bonding agents were not significant (p>0.05). It seems important for clinicians to use the combination of resin composite and dentin bonding agent recommended by the manufacturer.